Fábrica de adequação de conteúdos de ensino para objetos de aprendizagem reutilizáveis (RLOs) respeitando a norma SCORM - Kratz, Ricardo de Andrade (Universidade do Vale do Rio do Sinos, 2006)
To promote learning object reusability it is necessary to provide the normalization of its contents so that they can work appropriately in any e-learning system. The normalization alows easy reusability, portability of created contents, standardization of processes of creation, and management of learning objects. However, to normalize an existing E-learning environment it is not a trivial task and it requires adequacy either of the learning contents and the e-learning system, once the whole architecture is modified, being necessary though to separate the content from the structure. This research proposes and implements an architecture caled Adequacy Factory which is capable of promoting the interoperability of educational contents and the adequacy of educational resources for Learning Object Reusability, respecting the SCORM norm by using technologies such as Soft-ware Agents, Meta-Data (SCORM), and Web Services which make use of autonomy mechanism, interaction, invocation, access, and reuse of services
Keywords: agentes de software; agentes de web services; educação à distância; engenharia de Software; objetos de aprendizagem; agents web services; e-learning; learning objects; software agents; software engineer; Ciências Exatas e da Terra